(untitled) (Latin American Journal of Sedimentology and Basin Analysis, 2021)
Along the coast of the Southeastern Buenos Aires Province (Fig. 1), there are two important geomorphologic relieves: low sandy beaches with dune fields, and pocket beaches located between loessic or quarcitic cliffs. To the North and South of Mar del Plata City, extense dune fields conform the Eastern and Southern barriers. These dune fields are very modern, since they have been formed as consequence of a Holocene sea-level fluctuation (Schnack et al., 1982; Violante and Parker 1993; Isla, 1997). The objective of the study was to analyse the natural and artificial morphological changes of the beaches of Pinamar, Villa Gesell, Mar Chiquita, General Pueyrredón, General Alvarado, Lobería and Necochea counties, and the description and discussion of results obtained from 1983 to 2004. Special emphasis was made to the sedimentary dynamics of these beaches and the changes induced by man-made structures (groynes fields) and sand mining. The beaches have different orientation, dynamics, grain size, as well as different human alteration degree. The work was based on the comparison of beach profiles according to conventional methods (Fox and Davis, 1978; Isla, 1992; Isla et al., 1994; Bértola, 2001), the evaluation of the morphological classification based on Dean’s number (Dean, 1973), Omega parameter (Masselink and Short, 1993), Battje´s number (Short, 1996), and the parameter of Guza and Inman (1975). Surface grain sizes were analysed using the parameters of Folk and Ward (1957) and evaluating beach slope changes. North Area Morphology: These are oceanic beaches, with average width of 72 m., The berm remains stabilised or it is in setback. Berm width increases at the touristic area in Mar de las Pampas. Villa Gesell beaches (Spa Los Históricos) suffered significant variations. In the pristine areas, there is presence of dunes after the backshore, although many of them are forested. Balance: In this area, there are no structures or estuaries that could affect the littoral drift. The Pinamar-Cariló sector has recorded an important accumulation (27,580 m3) diminishing toward the North of the urban area. The beach of Villa Gesell has also registered accumulation (18,200 m3), except in certain areas of the centre of the urban area, where erosion existed. Toward the South of Mar de las Pampas, the trend is depositional again. Grain sizes: The sediments of the backshore have increased their size up to 1994 and begin stable since 2000. In the foreshore, the mean (phi) has a reduction tendency. It diminished from 1994 to 1996 where it stops then increases very slowly. In some samples of Mar de las Pampas and Mar Azul, bioclastic composition dominates that would indicate a source of contribution from the South that coincides with old places of extraction of sands for construction. In addition, to the South of Villa Gesell, the erosion of dunes exhumes old beach crests or non-operative overwash composed by sand with shells and gravels (Isla, 1998). Slopes: Slope increases from South to North, with anomalous values in the centre of Pinamar. Temporarily, the general slopes increase their value in the time since 1998. Central Area Morphology: General Pueyrredón beaches change from North to South in: a) beaches among closed groynes, b) artificially refilled beaches, c) oceanic open beaches, and d) beaches at the foot of cliffs; in Miramar there are also beaches among groynes, but these with more spacing to each other (e). Beaches between groynes characterise La Perla area, with average widths of 64 m. Beach fills were conducted from Playa Popular to Playa Grande, their widths are of 107 m. The oceanic beaches extending from Mar del Plata Harbour to the Punta Mogotes Lighthouse and have 102 m. Beaches at the foot of cliffs (Costa Hermosa to Los Acantilados) are narrow, about 60 m. Those beaches between groynes from Chapadmalal to Miramar are 75 m. The beaches oriented to the Southeast have higher dynamics (Alfar, Chapadmalal and Miramar) with volumetric variations of the order of several thousands of cubic meters. Some have anthropic action that modifies totally and in a few days their morphology, for what we should absorb of the seasonal effects of erosion in winter and accumulation in the analysis of the results in spring. To the end of winter, beaches recover. Balance: The beaches of General Pueyrredón and Miramar are mixed and complex. There are pocket beaches, and beaches with abrasion plains; there is an important component of constructions of coastal defences. Mar del Plata beaches recorded an erosive trend (-2.266 m3) excluding the refilled volumes of 1998. This demonstrates the natural eroded tendency in the beaches without artificial feeding. Toward the North of the urban area of Mar del Plata there is accumulation, in their Central section there is erosion and toward the South of the urbanisation (Punta Mogotes Lighthouse) there is accumulation again. To the South -cliff areas-, erosion dominates. As expected, the highest variability was recorded at the refilled beaches, but there are significant dynamics at other of them (Acevedo, Spa Camping El Faro and Los Acantilados). General Alvarado beaches registered an important accumulation of 28.000 m3 of sand, of which 20% belongs to the urban coastline of Miramar (Spa HR). Grain sizes: In these beaches, the sediments have gone increasing the mean from 1998. The beaches increased the size of their sands toward the North, with fine grains in the refilled beaches and for the effect of tombolo in Los Pinos Beach (Alfar). In some samples of Chapadmalal, coarse grains of basaltic and andesitic composition have been detected in the bottom of the backshore, and pebbles of loess in the top of the backshore. This would indicate a particular dynamics that accumulates rolling stones transported by coastal drift from the South, the first one presumably of patagonic pebbles and of eroded material of the cliff bordering, in the second. Slopes: Beach slopes decrease from North to South, with abrupt peaks in the centre of the urban areas of Mar del Plata. The extreme values in the slopes were observed in the resort places from the downtown. Temporarily, the variations in the slopes were very important; in general a tendency was appreciated to increase the slope of the general beach along the time (except in beaches like Alfonsina, Las Dunas and Los Acantilados). South Area Morphology: The beaches of this area are open and with Loess cliffs. From Miramar to Mar del Sur beach widths extend to 79 m, and from Mar del Sur to Necochea they are narrower (68 m). Touristic activities diminish southwards. The beaches with more dynamics are those that possess groynes, cliffs and abrasion plains, as long as the beach open of Cruz del Moro has had smaller volumetric variations. Some beaches have suffered anthropic action (Costa Bonita or Cruz del Moro) that modified their morphology. Balance: They are heterogeneous beaches, with cliffs and engineering works in Mar del Sur and Costa Bonita, and open beaches in Cruz del Moro and Arenas Verdes. It begins to be important the action of the streams that in certain cases obstruct the longshore drift or they are plugged by effect of the same one. In General Alvarado accumulation is appreciated toward the North and South of the urban area of Miramar, with an important accumulation in Mar del Sur. Lobería presents erosion in its entire coast (-14.746 m3) with more loss in its Eastern sector. Costa Bonita beaches have more dynamics and Cruz del Moro suffer less variability. In both municipalities, erosion cycles and accumulation were observed along the year in correspondence to seasonal variations. Grain sizes: In the beaches of this area, an increase of the value of the mean is appreciated from 1995. In the backshore, grain size diminishes toward the South and in the foreshore, increase toward the South. Slopes: Slopes increase from North to South. With relationship to the foreshore, the slopes are had increasing through the time and all the beaches have had important variations equally. In the discussion, morphodynamics and grain sizes were evaluated, considering specially the dynamics of beaches composed of sand and gravel. The human impact was evaluated in relation to groin construction, nourishment works, buildings at the beach, dune afforestation and sand mining. The conclusions sustain the idea of four interaction processes: 1) seasonal cycles, 2) storms and flood effects, 3) human impact, 4) presence of sand ridges that modify the angle of incidence of the waves producing local effects. The refilled beaches have passed of being reflective to dissipative; as it has only modified slopes and grain size (but not climate of waves), there is still erosive. Erosive beaches have higher slopes (more than 4%). The increase of the slope toward the North indicates more narrow beaches with smaller areas of dry sand. Southeastern beaches are therefore more vulnerable to storm effects. The differential refraction of the waves in the Southeast, generates the continuous energy concentration in certain places of the coast (for example the cliffs in Mar del Plata). Induced for sand ridges there is convergence -erosion- and divergence -sedimentation- of orthogonal separated by few kilometres of distance. The protection of the coast cannot be considered as an individual responsibility, and for it, although local solutions exist, they don’t work to regional scale; therefore, the coastal defence should be a cooperative effort among all the coastal municipalities.